New species of Bulbostylis (Cyperaceae) from South America - Paula Do Nascimento Prata, Ana; Gabriela López, M.; Wayt Thomas, William (Phytotaxa, 2017)
During the revision of the genus Bulbostylis for Brazil four new species were found, which are proposed here. Bulbostylis amazonica, B. decidua, B. minensis and B. wanderleyana are fully described, illustrated, and compared to other South American species.